2004
DOI: 10.1167/iovs.03-0733
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Increases Size and Severity of Experimental Choroidal Neovascularization

Abstract: Nicotine increases size and severity of experimental CNV in the present mouse model, possibly by potentiating PDGF-mediated upregulation of proliferation of choroidal smooth muscle cells or by other mechanisms. These results suggest that non-neuronal nicotinic receptor activation probably mediates some of the harmful effects of cigarette smoking in wet AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 47 publications
7
87
0
2
Order By: Relevance
“…7 It is postulated that smoking affects the pathogenesis of AMD by a variety of methods including promoting oxidative damage, inducing angiogenesis, impairing the choroidal circulation, and by activating the immune system including complement pathway. [8][9][10][11][12][13] Stopping smoking reduces the risk of AMD and after 20 years of cessation the risk of developing AMD is the same as for non-smokers. 14 In the last few years, the genetic factors significantly contributing to AMD risk have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is postulated that smoking affects the pathogenesis of AMD by a variety of methods including promoting oxidative damage, inducing angiogenesis, impairing the choroidal circulation, and by activating the immune system including complement pathway. [8][9][10][11][12][13] Stopping smoking reduces the risk of AMD and after 20 years of cessation the risk of developing AMD is the same as for non-smokers. 14 In the last few years, the genetic factors significantly contributing to AMD risk have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 and MMP-9 are the two major enzymes that can selectively degrade type IV collagen and facilitate tumor invasion and metastasis in various experimental models, including gastric, colon, and breast cancers (19)(20)(21). Administration of nicotine increased the severity of choroidal neovascularization and also reversed the VEGF-induced suppression of MMP-2 activity in mice (22), showing that MMP could play a role in the angiogenesis induced by nicotine. Indeed, suppression of MMP by different inhibitors markedly reduced tumor cell invasiveness and metastasis (23).…”
Section: Introductionmentioning
confidence: 99%
“…Both 11-Z-and 9-Z-retinoids are metabolic intermediates in vision and gene regulation, respectively, and strict homeostatic control is essential for proper function. Although oxidative stress and nicotine receptor activation may also play a role in the development of tobaccoassociated pathologies (36), the discovery that a nicotine metabolite catalyzes the isomerization of Z-retinals to all-E-retinal provides chemical evidence for an unrecognized mechanism of smoking toxicity. Specifically, the accumulation of all-E-retinal feeds the A2E biosynthetic pathway and leads to lipofuscin of RPE cells and ultimately age-related macular degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent genomic studies have shown that a genetic predisposition for age-related macular degeneration is manifested in complement factor H polymorphisms (30)(31)(32), the primary environmental factor contributing to age-related macular degeneration is cigarette smoking (33)(34)(35). Indeed, mice administered nicotine as a dietary supplement were shown to have an increased incidence of age-related macular degeneration (36).…”
mentioning
confidence: 99%